Strategi Mengembangkan Materi dan Metode Pembelajaran Bahasa Arab - Muhammad Roqib (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: This paper describes the importance the Arabic language to be learned by using good strategies and methods. Language as a medium of communication greatly affect’s a person success. Use this of strategy, based on several succeses that have been undertaken for example by Pondok Gontor and UIN Malang. However, the practice of application of strategies and methods are actually very diverse. Awareness of educators and learners to motivate each other in the practice of matering the Arabic language becomes very important. Moreover, the habit of the learner in the environment and the daily use of Arabic is very determining factor in learning the Arabic seriousness. This paper describes more about the methods that can be applied, adapted to the situation and condition. Different situations and conditions, requires different strategies and methodes as well. Keywords: Strategy, Development, Method, Learning, and Arabic.